Wind Ventilator Utilization for Electrical Mini Power Plant: Residential Lighting - Suryadi, Aris; Notosudjono, Didik; Hanafi, Dirman (International Journal of Integrated Engineering, 2021)
The development of renewable energy potential in Indonesia is actively carried out to obtain alternative energy sources along with the depletion of available fossil energy reserves. One of the green energy without polluting the environment is wind energy. Indonesia is an archipelago located in the tropics with a large potential source of wind energy, but until now it has not been optimal enough to be used for electricity generation. Utilization of energy produced by the wind is by changing it into mechanical energy by using wind turbines. Furthermore, mechanical energy from the turbine will be used to drive a dc generator to produce electrical energy. As a simple application in this study, the wind ventilator in the form of a turbine that is mounted on the top of the house roof is applied to be a wind turbine. Ventilators will move if there is wind touches its blades and it will suck out the air in the house. The axis of the ventilator will be coupled to the dc generator using pulley and v-belt. So, when the ventilator rotates, the generator will also rotate and will produce electrical energy. The objective of this study is to meet the energy needs for lighting requirement of a house.  The experimental test results show that the use of ventilators as an alternative ways for the wind energy utilization is worked well.